2020
DOI: 10.1007/s12144-020-00648-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of parental control and coping strategies on adolescents’ problem behaviors

Abstract: The current study was aimed at contributing to the understanding of the role of perceived parental monitoring, psychological control, and coping strategies on adolescents' problem behaviors, in terms of anxiety and drinking behavior. Participants were 541 high school students, 17 to 19-year old (M = 17.09, SD = 0.80) high school students in Sicily and Calabria (Italy). Participants completed self-report measures assessing parental monitoring, psychological control, coping strategies (i.e., Task-Oriented, Emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 115 publications
(184 reference statements)
2
9
0
Order By: Relevance
“…Consistent with our hypotheses, negative concurrent associations were observed between both parents' BC and adolescent delinquency. The findings are in line with the general conclusion that BC benefits child development, which has been widely supported by previous cross-sectional and longitudinal associations between levels of parents' BC and adolescent problem behavior [4,45,46]. Our investigation expands this relationship pattern to the rate of changes.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our hypotheses, negative concurrent associations were observed between both parents' BC and adolescent delinquency. The findings are in line with the general conclusion that BC benefits child development, which has been widely supported by previous cross-sectional and longitudinal associations between levels of parents' BC and adolescent problem behavior [4,45,46]. Our investigation expands this relationship pattern to the rate of changes.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, international research has shown that the lack of parental warmth, emotional support, and behavioral control are associated with a wide range of youth’s externalizing problems, including aggression [ 35 , 36 ], addictive behaviors [ 37 , 38 , 39 ], and risk-taking [ 40 , 41 ]. Recently, the same associations have been reported also with antisocial traits and delinquency [ 42 , 43 , 44 , 45 ], but focusing almost exclusively on adolescent samples. Only a few studies have explored the association between family functioning and ASPD symptoms among the emerging adulthood population [ 14 , 15 , 16 , 17 , 46 ], although the important role played by emerging adults’ family functioning for their psychological well-being has been widely shown [ 33 , 47 ].…”
Section: Introductionmentioning
confidence: 62%
“…This study aimed to further increase the knowledge on protective and risk factors involved in antisocial personality problems in emerging adulthood. To this end, we have chosen to focus on relational and individual variables (i.e., family functioning, impulsivity, and empathy) that previous literature on adolescent and adult populations has indicated as significant predictors of both personality [ 48 , 49 , 54 , 55 , 56 ] and behavior features [ 44 , 45 , 52 , 80 , 81 ] of antisociality. In addition, we tested a conceptual framework that took into consideration the complex relationships between these variables, considering both the direct effect of family functioning and indirect effects via emerging adults’ impulsivity and empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Suwarni, Ismail, Prabandari, and Adiyanti (2015) found that parental monitoring related to sexual behavior was another important factor to control the attitude toward premarital sexual behaviours among adolescents. Parental monitoring influences attitudes about adolescent sexual behaviour (Inguglia, Costa, Ingoglia, Cuzzocrea, & Liga, 2020;Rostiawan, Yusuf, & Dahlan, 2020;Tomić, Burić, & Štulhofer, 2018). However, in Indonesia, providing information about premarital sex is still considered taboo because parents are worried that when providing information about sex means parents teach their children to have sexual relations.…”
Section: Introductionmentioning
confidence: 99%